2019
DOI: 10.1080/10717544.2019.1686086
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oral absorption improvement for insoluble drugs by the combination of phospholipid complex and SNEDDS

Abstract: In the present study, a water insoluble drug named silybin was encapsulated into self-nanoemulsifying drug delivery system (SNEDDS) following the preparation of silybin-phospholipid complex (SB-PC), then several methods were carried out to characterize SB-PC-SNEDDS and elucidate its mechanisms to improve the oral absorption of SB. Using a dynamic in vitro digestion model, the lipolysis of SB-PC-SNEDDS was proved to be mainly related with the property of its lipid excipients. SB-PC-SNEDDS could significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Based on increasing understanding of involved mechanisms, lymphatic transport has become an important approach in drug discovery. Table 1 39 , 171 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 summarizes examples of application of lymphatic transport in oral drug delivery for reduced first-pass effect, facilitated oral absorption, distant organ targeting and lymphatic associated treatment.…”
Section: Application Of Lymphatic Transport In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on increasing understanding of involved mechanisms, lymphatic transport has become an important approach in drug discovery. Table 1 39 , 171 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 summarizes examples of application of lymphatic transport in oral drug delivery for reduced first-pass effect, facilitated oral absorption, distant organ targeting and lymphatic associated treatment.…”
Section: Application Of Lymphatic Transport In Drug Deliverymentioning
confidence: 99%
“…N -carboxymethyl chitosan-coated SLNs showed more than 4-fold and near 2-fold increase in lymphatic transport of curcumin in comparison with curcumin solution and uncoated SLNs, respectively, echoing the capacity of opening tight junction and lymphatic transport via the paracellular pathway 212 . It is acknowledged that besides improved dissolution and permeability, lymphatic transport also plays a role in enhanced oral absorption of several successfully marketed lipid-based products 69 , 213 , 214 , 231 . Multiple mechanisms, though difficult to clarify, may act concurrently in lymphatic transport.…”
Section: Application Of Lymphatic Transport In Drug Deliverymentioning
confidence: 99%
“…Caco-2 cells can be pretreated with different inhibitors to elucidate the uptake mechanisms of drugs and lipid nanocarriers [ 50 , 171 ]. Several studies have shown enhanced drug permeation from SNEDDSs using Caco-2 monolayers [ 172 , 173 , 174 , 175 , 176 ]. Memvanga et al [ 40 ] demonstrated that the transport of the curcumin-SEDDSs across Caco-2 monolayers was improved compared with that of free drug ( Figure 5 e).…”
Section: In Vitro Assessment Of Sneddss Formulationsmentioning
confidence: 99%
“…These are described as clear systems that consist of oils, surfactants, co-surfactant, which result in ultrafine oil/water emulsion with mean globule size distribution <100 nm upon emulsification in the gastric milieu (Gahlawat et al, 2019). They help in possessing higher solubilization capacity, leading to the addition of medicament inside the oil phase (Khalifa et al, 2019;Tong et al, 2019;Kuncahyo et al, 2019). The excipients contained in the SNEDDS tend to facilitate bioavailability of the drugs not merely by improving drug solubility and permeability but by circumventing the metabolism by liver microsomes and inhibiting P-gp efflux, along with the ability to facilitate lymphatic drug absorption.…”
Section: Introductionmentioning
confidence: 99%